An intelligent approach to non-constant feed rate determination for high-performance 2D CNC milling. (15th June 2006) - Chen, Zezhong C.; Miao, Zhibin
Optimal machining parameters (spindle speed, feed rate, and depth of cut) are crucial to high-performance CNC pocketing and profiling, which is concerned with shorter machining time, higher surface quality, and longer tool life. However, the feed rates are often conservatively fixed, obviously un-optimised, for different geometries of a curved profile. In this work, an intelligent approach to determining non-constant feed rates is proposed. First, the geometric features of this profile are identified, and the corresponding effective radial depths of cut are calculated. Second, based on a database of these machining parameters, a fuzzy rule-based system is established to predict various cutting forces along this profile. Then the feed rates are adjusted so that the cutting forces always remain high and chatter is still prevented. Thus the high-performance machining can be realised by using this approach, which can also be readily implemented in production process planning to benefit the manufacturing industry.